The Relationship between Anxiety and The Behaviour of Parents in Bringing Their Children to be Immunized During the COVID-19 Pandemic - Jayanti, Ni Wayan Radha Rani; Devi, Ni Luh Putu Shinta; Utami, Ni Kadek Cahya; Puspita, Luh Mira (Babali Nursing Research, 2024)
Introduction: The Covid-19 pandemic causes fear and concern for parents to be infected with Covid-19 if they come to the Posyandu or health care facilities for immunization. The purpose of this study was to determine the relationship between anxiety and the behavior of parents in bringing their children immunized during the Covid-19 pandemic in the work area of Puskesmas III Denpasar Selatan. Methods: This study was a descriptive correlational study with a cross sectional approach. The sampling technique was used non-probability sampling with purposive sampling technique. The sample used 71 parents which have babies and toddlers with the age of 0-24 months. The data were collected in the work area of Puskesmas III Denpasar Selatan for one month from March to April 2022. The research instruments used were the Covid-19 Pandemic Anxiety Questionnaire and the Immunization Behavior Questionnaire During the Covid-19 Pandemic. Results: Spearman rank correlation test result showed that there was a significant relationship between anxiety and the behavior of parents in bringing their children immunized during the Covid-19 pandemic in the work area of Puskesmas III Denpasar Selatan (p value = 0.000; r = -0.858). Conclusion: Health workers are expected to be able to provide information to parents who have babies and toddlers about the importance of bringing their children immunized during the Covid-19 pandemic.